Hypersensitivity and in-stent restenosis in coronary stent materials - Hu, Wansong; Jiang, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Coronary heart disease(CHD) is a type of cardiovascular disease with the highest mortality rate worldwide. Percutaneous translu-minal coronary intervention (PCI) is the most effective method for treating CHD. However, in-stent restenosis (ISR), a long-term complication after PCI, affects the prognosis of patients with CHD. Previous studies have suggested that hypersensitivity reactions induced by metallic components may be one of the reasons of this complication. With the emergence of first- and second-generation drug-eluting stents(DES), the efficacy and prognosis of patients with CHD have greatly improved, and the incidence of ISR has grad-ually decreased to less than 10%. Nevertheless, DES components have been reported to induce hypersensitivity reactions, either indi-vidually or synergistically, and cause local inflammation and neointima formation, leading to long-term adverse cardiovascular events. In this article, we described the relationship between ISR and hypersensitivity from different perspectives, including its possi-ble pathogenesis, and discussed their potential influencing factors and clinical significance.